Mutations of the cystic fibrosis transmembrane conductance regulator gene in males with congenital bilateral absence of the vas deferens: Reproductive implications and genetic counseling - Cui, Xiangrong (Mol Med Rep, 2020)
Congenital bilateral absence of the vas deferens (CBAVD) is predominantly caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene. CBAVD accounts for 2–6% of male infertility cases and up to 25% of cases of obstructive azoospermia. With the use of pre-implantation genetic diagnosis, testicular or epididymal sperm aspiration, intracytoplasmic sperm injection and in vitro fertilization, patients affected by CBAVD are able to have children who do not carry CFTR gene mutations, thereby preventing disease. Therefore, genetic counseling should be provided to couples receiving assisted reproductive techniques to discuss the impact of CFTR gene mutations on reproductive health. In the present article, the current literature concerning the CFTR gene and its association with CBAVD is reviewed.